Highly Luminescent 2D‐Type Slab Crystals Based on a Molecular Charge‐Transfer Complex as Promising Organic Light‐Emitting Transistor Materials. Issue 36 (26th July 2017) - Park, Sang Kyu; Kim, Jin Hong; Ohto, Tatsuhiko; Yamada, Ryo; Jones, Andrew O. F.; Whang, Dong Ryeol; Cho, Illhun; Oh, Sangyoon; Hong, Seung Hwa; Kwon, Ji Eon; Kim, Jong H.; Olivier, Yoann; et al.
Abstract : A new 2:1 donor (D):acceptor (A) mixed‐stacked charge‐transfer (CT) cocrystal comprising isometrically structured dicyanodistyrylbenzene‐based D and A molecules is designed and synthesized. Uniform 2D‐type morphology is manifested by the exquisite interplay of intermolecular interactions. In addition to its appealing structural features, unique optoelectronic properties are unveiled. Exceptionally high photoluminescence quantum yield ( Φ F ≈ 60%) is realized by non‐negligible oscillator strength of the S1 transition, and rigidified 2D‐type structure. Moreover, this luminescent 2D‐type CT crystal exhibits balanced ambipolar transport ( µ h and µ e of ≈10 −4 cm 2 V −1 s −1 ). As a consequence of such unique optoelectronic characteristics, the first CT electroluminescence is demonstrated in a single active‐layered organic light‐emitting transistor (OLET) device. The external quantum efficiency of this OLET is as high as 1.5% to suggest a promising potential of luminescent mixed‐stacked CT cocrystals in OLET applications. Abstract : A novel 2D‐type slab crystal based on 2:1 donor:acceptor mixed‐stacked charge‐transfer (CT) complex is developed. Unique optoelectronic properties: balanced ambipolar transport ( µ e, µ h ≈ 10 −4 cm 2 V −1 s −1 ) and bright luminescence ( Φ F ≈ 60%) are successfully bridged in organic field‐effect transistor (OFET) devices, demonstrating the first CT organic light‐emitting transistors with high external quantum efficiency up to 1.5%.